Variables influyentes en el proceso de lixiviación para la recuperación de metales contenidos en lodos galvánicos (2018)
In the present article present a bibliographic review concerning the operation variables involved in the leaching process is developed, which allows to identify the effects that they have on the recovery percentage of metals contained in galvanic residues, consequently, the leaching method, leaching agents and their concentration, use of an oxidizing agent, granulometry of the solid, mineral concentration, temperature and stirring speed were identified as influential variables, additionally, it was found that for most of the authors like Jha, Kim, Ranitovic, Yang, among others , the results obtained lead, generally, to a recovery of more than 90% of the metal of interest.